PROVISION OF INFORMATION IN PUBLIC PROCUREMENT - Skrastiņa, Una; Radzevičs, Juris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The provision of information in public procurement is the only way for both society and tenderers to obtain information about the legitimate process of public procurement. Since the exchange of information is regulated by the Public Procurement Law and other laws and regulations, it is not always clear for the involved parties how to apply this regulation in practice. As a result, information that could be accessed and received in a timely manner and could be used to defend tenderers’ interests is not asked for, and the tenderers frequently request information that is of restricted accessibility or is not unclassified. The aim of this research is to analyse the legal regulation of information provision in the public procurement field in Latvia, to detect the most common problems in practice and to give possible solutions to them. Tasks - to study the legal regulation, legal scientists’ views, problems in practice and, gathering the information, to give possible solutions to them. The descriptive, dogmatic, historical, comparative and analytical research methods were used in this research. Results - two important principles can conflict when providing information – the principle of transparency and competition. So the contracting authority should evaluate in each situation, which of them should be more important.